NADPH Oxidase Activation Contributes to Heavy Ion Irradiation-Induced Cell Death - Yupei Wang; Qing Liu; Weiping Zhao; Xin Zhou; Guoying Miao; Chao Sun; Hong Zhang (SAGE Publishing, 2017)
Increased oxidative stress plays an important role in heavy ion radiation-induced cell death. The mechanism involved in the generation of elevated reactive oxygen species (ROS) is not fully illustrated. Here we show that NADPH oxidase activation is closely related to heavy ion radiation-induced cell death via excessive ROS generation. Cell death and cellular ROS can be greatly reduced in irradiated cancer cells with the preincubation of diphenyleneiodium, an inhibitor of NADPH oxidase. Most of the NADPH oxidase (NOX) family proteins (NOX1, NOX2, NOX3, NOX4, and NOX5) showed increased expression after heavy ion irradiation. Meanwhile, the cytoplasmic subunit p47 phox was translocated to the cell membrane and localized with NOX2 to form reactive NADPH oxidase. Our data suggest for the first time that ROS generation, as mediated by NADPH oxidase activation, could be an important contributor to heavy ion irradiation-induced cell death.